2013
DOI: 10.1007/978-81-322-1160-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Aluminum-Doped ZnO Films by ICP-Assisted Sputtering

Abstract: Inductively coupled plasma (ICP) assisted DC sputter-deposition was used for the deposition of Al-doped ZnO (AZO or ZnO:Al) thin films. With increasing ICP RF power, film properties including deposition rate, crystallinity, transparency and resistivity were improved. To understand the plasma-surface interaction, several plasma diagnostics were performed. Heat fluxes to the substrate were measured by thermal probes, number densities of sputtered metallic atom species were measured by absorption spectroscopy usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…According to the recent our measurements of working Ar gas temperature 28) using tunable diode laser absorption spectroscopy, 29,30) the accidental difference in J total and J ch recognized in Figs. 6 and 8 may be explained by J n .…”
Section: Spatial Profile Of J Total Measured With a Compact Tp2mentioning
confidence: 99%
“…According to the recent our measurements of working Ar gas temperature 28) using tunable diode laser absorption spectroscopy, 29,30) the accidental difference in J total and J ch recognized in Figs. 6 and 8 may be explained by J n .…”
Section: Spatial Profile Of J Total Measured With a Compact Tp2mentioning
confidence: 99%
“…Indium-free metal-doped zinc oxide, Ga− or Al-doped ZnO (GZO, AZO) is attractive as an environmentally friendly transparent conductive oxide and is expected to be one of the candidates to replace ITO. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] A problem with planar magnetron sputter deposition using oxide targets is that the film composition and crystallinity on the substrate surface opposite the eroded area of the target is reduced. This has multiple causes.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted so far to overcome these problems with the goal of substituting ITO with metal-doped ZnO. To further lower the resistivity and flatten the resistivity spatial distribution, it is reported that the following are effective: addition of hydrogen gas, 13,14) substrate heating during film formation, 15,16) post annealing, 17) formation of an intermediate buffer layer between thin film and substrate, [18][19][20] off-axis arrangement of substrate, 21) use of facing targets, 22,23) superposition of DC and RF, 16,[24][25][26] utilization of inductively coupled plasma assist, [27][28][29] installation of mesh grid between target and substrate, 30) etc.…”
Section: Introductionmentioning
confidence: 99%